HUBUNGAN PENGETAHUAN, PERSEPSI KESERIUSAN, PERSEPSI HAMBATAN DAN EFIKASI DIRI DENGAN PARTISIPASI REMAJA DALAM MENGIKUTI POSYANDU REMAJA - Kika Dwi Kurniawati; Aditya Kusumawati; Priyadi Nugraha Prabamurti (Jurnal Kesehatan Masyarakat (Undip), 2020)
Posyandu remaja is one of the forms of Community-Based Health Efforts (UKBM) which is managed and organized from, by, for and with the community including youth in organizing health development, in order to empower the community and provide facilities in obtaining health services for adolescents to improve their health and skills teenage healthy life. Posyandu remaja is an extension of PKPR program implemented by puskesmas. The purpose of this study was to analyze the factors related to the participation of adolescents in participating in posyandu remaja in the Panggung Kidul Village. This research uses quantitative research with cross-sectional approach. The population in this study were adolescents in the Village of Panggung Kidul with a total of 836 adolescents and then samples were taken as many as 100 adolescents using the Propotional Random Sampling method. This study used univariate and bivariate analysis with the Chi Square test. This research was conducted after obtaining ethical approval from the Health Research Ethics Commission of the Faculty of Public Health, University of Diponegoro under number 442 / EA / KEPK-FKM / 2019.The results showed that knowledge (p-value = 0.013), perception of seriousness (p-value = 0.009), perception of obstacles (p-value = 0.003) and self-efficacy (p-value = 0.003) were related to adolescent participation in participating in posyandu remaja. It is hoped that Bulu Lor Health Center can improve information on the form of services provided by Posyandu remaja and there is a need for training and the formation of new cadres. In addition, there is still a need for an active role from Posyandu remaja cadres to provide more varied material.